Social movements in the digital age: A bibliometric analysis of strategies and structures in achieving social change - Asmiyono, Elzania; Rahmawati, Dian Eka (Masyarakat, Kebudayaan dan Politik, 2025)
The digital era has significantly transformed how societies engage in social movements by introducing innovative tools and platforms. This study analyzes the role of non-social media digital technologies, such as blockchain, online petition platforms, and crowdfunding systems, in fostering inclusive and sustainable social movements. Using qualitative methods with bibliometric analysis, this research investigates the strategic and structural transformation of social movements in the digital age. The findings highlight that while blockchain offers transparency in fundraising and decision-making processes, platforms like Avaaz and Change.org enhance public participation and legitimacy in advocacy. Crowdfunding platforms provide financial solutions for overlooked social projects, and applications like Open311 strengthen citizen-government relationships. Despite these benefits, challenges such as slacktivism, misinformation, and algorithmic biases remain significant barriers. The study concludes by proposing a blended approach, integrating digital and traditional offline strategies, to achieve impactful and sustainable social change. This research contributes to the literature by exploring underexamined digital tools beyond social media, providing actionable recommendations for activists, policymakers, and technologists.